The Symbolic Convergence of Crowdfunding in Political Campaigns (Case Study: Netizen Discussions On Ridwan Kamil‘S Facebook Fanpage) - Rindana Intan Emeilia; Nani Nurani Muksin (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2020)
Internet plays an important role as a medium of political communication, including its power forfunding political campaigns known as crowdfunding. The success of crowdfunding inseveral countries,thenadopted by West Java volunteers to raise funding political campaigns for Ridwan Kamil and Uu Ruzhanul Ulum in 2018 Governor Election. Socialization was carried out by uploading a video on title Udunan Warga (Funding from the Residents) which caused political discussion among virtual communities on Ridwan Kamil‘s Facebook. The existence of virtual communities in discussing political fundraising campaign ideas has an important role in supporting crowdfunding success.The reason is virtual communities have a potentialto discuss shared interests and are very likely to have shared group consciousness to support crowdfunding movements.This article aims to explain how the crowdfunding mechanism carried out by West Java Volunteers and how the process symbolic convergence of netizens related to raise funding political campaign on Ridwan Kamil’s Facebook which presents shared group consciousness. This study uses a case study method and data collection techniques using online observation, interviews and documentation. The theory used was symbolic convergence which was popularized by Ernest Bormann to see the construction of shared consciousness among the netizens after seeing the video of Udunan Warga (Funding from the Residents). The results showed that (1) the crowdfunding mechanism carried out involved West Java volunteer as fundraisers, the site https://jabarjuara.id as intermediary platform and netizens as donors; (2) the process of crowdfunding symbolic convergence on Ridwan Kamil’s Facebook took place in stages ranging from basic structure, message structure, dynamic structure, communicator structure, medium structure and evaluative structure. A rhetorical vision appeared in relation to the basic message, namely “Dukung Udunan WargaDemi Jabar Juara” (support crowdfunding for West Java become champions). Then rhetorical visionsucceededin raising shared group consciousnesswhich notonly supported crowdfunding atthe discourse level but also donated their money for the campaign costs of Ridwan Kamil and Uu Ruzhanul Ulum.